THE LEADERSHIP OF PRIESTS IN THE LIGHT OF CANON 255 THE 1983 CODE - Pandego, Higianes Indro; Purba, Asrot; Marmidi, F.X. (LOGOS, 2025)
Leadership is one of the important topic when people discuss on the organization. A good development is determined by a good and a strong leadership. The same thing when we talk about the (Catholic) Church. That is the reason of this thesis in which the writer wants to describe that the Church as a spiritual institution and social structure needs a strong leadership. Departing from can. 255, the researcher will explain the threefold munus and the pastoral functions in which the priests fulfill their tasks. This research is different with others because on can. 255 any others thesis has focus on the pastoral aspect of priesthood. On the other hand, this thesis focus on the leadership of priests.